Coming - Van Reeth, Adele (Book collections on Project MUSE., 2017)
Coming is a lyrical, erudite examination of the French notion of jouissance. How did jouissance evolve from referring to the pleasure of possessing a material thing (property, wealth) to the pleasure of orgasm, from appropriation to dis-appropriation, from consumption to consummation? The philosophers Adele van Reeth and Jean-Luc Nancy engage in a lively dialogue touching on authors as varied as Spinoza, Hegel, Saint Augustine, the Marquis de Sade, Marguerite Duras, and Henry Miller, and on subjects ranging from consumerism to video games to mysticism.